2017
DOI: 10.1111/obr.12623
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness‐based interventions for weight loss: a systematic review and meta‐analysis

Abstract: Results suggest that MBIs are effective in reducing weight and improving obesity-related eating behaviours among individuals with overweight and obesity. Further research is needed to examine their efficacy for weight loss maintenance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
118
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(138 citation statements)
references
References 79 publications
5
118
1
4
Order By: Relevance
“…Genetic contributions to socialization processes and developmental outcomes could be expressed directly or through child temperament. 96,138 Temperament has been described as a term for "biologically based individual differences in behavior that become children's basic personality" 96 p. 372 and as the physiological basis for individual differences in reactivity and self-regulation, including motivation, affect, activity, and attention characteristics. 138 p. 253 Temperament is an umbrella construct for deeply rooted predispositions that emerge early in life and are relatively stable.…”
Section: Child Temperament and Its Role In Behavior Development Ementioning
confidence: 99%
See 1 more Smart Citation
“…Genetic contributions to socialization processes and developmental outcomes could be expressed directly or through child temperament. 96,138 Temperament has been described as a term for "biologically based individual differences in behavior that become children's basic personality" 96 p. 372 and as the physiological basis for individual differences in reactivity and self-regulation, including motivation, affect, activity, and attention characteristics. 138 p. 253 Temperament is an umbrella construct for deeply rooted predispositions that emerge early in life and are relatively stable.…”
Section: Child Temperament and Its Role In Behavior Development Ementioning
confidence: 99%
“…These strategies are consistent with a recent focus on the contribution of mindfulness to obesity in adults 206 and mindfulness-based interventions with adults. 372 Evidence about processes associated with the development or disruption of abilities to self-regulate energy intake from infancy to middle childhood should enable intervention and prevention strategies to focus on the relevant child and family processes at this age rather than subsequent corrective interventions targeted only at the child, adolescent or adult.…”
Section: Towards Prevention and Intervention Strategiesmentioning
confidence: 99%
“…However, the evidence of their superior effectiveness is less clear. Previous systematic reviews and meta‐analyses primarily focused on mindfulness‐ and/or acceptance‐based interventions . Three reviews have reported a quantitative synthesis of pre‐intervention to post‐intervention change without comparing the effect against a comparator.…”
Section: Introductionmentioning
confidence: 99%
“…Previous systematic reviews and meta‐analyses primarily focused on mindfulness‐ and/or acceptance‐based interventions . Three reviews have reported a quantitative synthesis of pre‐intervention to post‐intervention change without comparing the effect against a comparator. Two of these three reviews reported a “small” pre‐intervention to post‐intervention change in weight or body mass index (BMI) while the other study reported a null effect on BMI.…”
Section: Introductionmentioning
confidence: 99%
“…Dear Editor, We thank Dr. Bergman for her critique on our recently published manuscript 'Mindfulness-based interventions for weight loss: A systematic review and meta-analysis' (1). In reference to Dr. Bergman's comment regarding our use of the Preferred Reporting Items for Systematics Reviews and Meta-Analyses (PRISMA), we conducted the meta-analysis according to the PRISMA criteria and had provided the checklist as part of the submission process.…”
mentioning
confidence: 99%